Effects of stillage on soil pH, germination rate and potassium accumulation in corn - Santos, Gabriel A.; Rossiello, Roberto O. P.; Fernandes, Manlio S.; O’Grady, Paulo C. (Pesquisa Agropecuaria Brasileira, 2014)
A greenhouse study was conducted on the effects of increasing levels of soil applied stillage on soil pH, germination and growth patterns of corn (Zea mays L.). Stillage was applied to soil in pots, at levels corresponding to 0, 50, 100, 200, 400, 800 and 1.600 m3/ha. Plant germination decreased in 50% for the 800 m3/ha treatment and in 65% for the 1,600 m3/ha treatment. Stillage applications increased soil pH values, up to 0,99 pH unit. Up to the 800 m3/ha treatment, stillage applications increased the dry matter accumulation of both shoots and roots. At 1,600 m3/ha, a sharp decrease in dry weights of shoots and roots occurred. Plant potassium contents (expressed as percentage of dry weight), increased as the stillage applications increased and a positive relationship was found between plant-K and tissue succulence. At the same time, electrical conductivity of soil increased from 0,31 mmhos/cm for the 50 m3/ha treatment, to 7,95 mmhos/cm for the 1,600 m3/ha treatment. This increase in electrical, conductivity of the soil combined with the high plant-K content and tissue succulence, with increasing levels of stillage application, led to postulate that the increase in tissue succulence was the plant response to the increase in soil salinity.